Simultaneous quantitation of 17 endogenous adrenal corticosteroid hormones in human plasma by UHPLC-MS/MS and their application in congenital adrenal hyperplasia screening - Zhang, Qiaoxuan; Zhan, Min; Wu, Huihui; Feng, Pinning; Jin, Xing; Wan, Zemin; Yan, Jun; Zhang, Pengwei; Ke, Peifeng; Zhuang, Junhua; Zhou, Jiuyao; Han, Liqiao; et al. (Frontiers in Chemistry, 2022)
Accurate investigations of adrenal hormone levels play a vital role in pediatric endocrinology for the detection of steroid-related disorders. This study aims to develop a straightforward, sensitive UHPLC-MS/MS method to quantify 17 endogenous adrenal corticosteroid hormones in human plasma. These hormones are the mainly ingredient in the synthetic and metabolic pathways of adrenal corticosteroid hormones. Chromatographic separation was achieved on a C18 column be-fore electrospray ionization triple-quadrupole mass spectrometry in multiple reaction monitoring mode. The run time was 7 min. The sample preparation in this assay requires no derivatization and extraction by liquid-liquid extraction. Analytical performance was evaluated, including line-arity, analytical sensitivity, accuracy, precision, and specificity. Plasma specimens from 32 con-genital adrenal hyperplasia (CAH) patients and 30 healthy volunteers were analyzed to further reveal the diagnostic value of multiple steroid hormones in the synthetic and metabolic pathways of adrenal corticosteroid in CAH diagnosis. All hormones were effectively extracted and sepa-rated using our method. The method was essentially free from potential interference of isomers or structural analogues. The imprecisions were < 10%. The lower limits of quantification varied from 0.05 to 15.0 ng/mL. Good linearity coefficients (r2 > 0.998) were also obtained for most hor-mones in the required concentration range except for 21-deoxycortisol (r2 = 0.9967) and andros-tenediol (r2 = 0.9952). The recoveries for the steroid hormones ranged from 91.7% to 109.8%. We developed the UHPLC-MS/MS method for the simultaneous measurement of steroid hor-mones. The results showed that measurement steroid hormones simultaneously could improve the diagnostic efficiency of CAH.